Ferroelectric polymer thin-film memristors with asymmetric top electrodes. (1st July 2022) - Zhang, Ding-Guo; Gao, Xu; Tang, Wei; Zhong, Ya-Nan; Xu, Jian-Long; Wang, Sui-Dong
Abstract: A type of ferroelectric polymer thin-film memristors is demonstrated to show their potential in the emulation of synaptic plasticity. The memristive characteristics of the device arise from the design of asymmetric top electrodes capacitively coupled with a floating bottom electrode, which enables the local modulation of ferroelectric polarization in the ferroelectric terpolymer film. Basic synaptic functions, such as continuous increase/decrease in synaptic weight and paired-pulse facilitation, are successfully emulated using the ferroelectric polymer memristors. This work provides a promising approach to implementing ferroelectric mechanisms in electronic synapses.